Tax equalization in mutual funds - Gill, Steven Leigh (ScholarWorks@UMass Amherst, 2008)
Mutual funds are subject to a special set of income tax rules that provide a unique setting which facilitates an examination of the sharing of tax benefits between mutual fund managers and owners. By making an annual election, mutual funds can treat redemptions of shares as if they have been allocated a pro-rata share of taxable gains, when in fact they have not (known as "equalization"). This treatment allows a portion of the gains earned by mutual funds to go untaxed. This study shows that a fund's choice to equalize appears to be motivated by factors associated with the costs of equalization more so than the benefits. The tax savings are considered in making efficient investing decisions only by potential investors in funds with larger unrealized capital gains.